2004
DOI: 10.1073/pnas.0402623101
|View full text |Cite|
|
Sign up to set email alerts
|

Preferred peptide backbone conformations in the unfolded state revealed by the structure analysis of alanine-based (AXA) tripeptides in aqueous solution

Abstract: We have combined Fourier transform IR, polarized Raman spectroscopy, and vibrational CD measurements of the amide I′ band profile of alanyl-X-alanine tripeptides in 2 H 2 O to obtain the dihedral angles of their central amino acid residue. X represents glycine, valine, methionine, histidine, serine, proline, lysine, leucine, tryptophan, tyrosine, and phenylalanine. The experimental data were analyzed by means of a recently developed algorithm, which exploits the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
164
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(190 citation statements)
references
References 48 publications
(81 reference statements)
23
164
3
Order By: Relevance
“…Shi et al (24), for instance, used NMR and ECD measurements to study the structure of Ac-X 2 (A) 7 O 2 -NH 2 (XAO, X and O denote diaminobutyric acid and ornithine, respectively), and interpreted their results as indicating that the individual residues predominantly adopt a PPII conformation at room temperature. The results of Shi et al have been corroborated by numerous experimental and theoretical studies on short peptides, which all revealed a substantial PPII propensity for alanine (2,(4)(5)(6)(7)(8). This notion is also in perfect agreement with distributions that Serrano (25) and Avbelj and Baldwin (26) inferred from coil libraries, but at variance with a less restricted library investigated by Dobson and associates (27).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Shi et al (24), for instance, used NMR and ECD measurements to study the structure of Ac-X 2 (A) 7 O 2 -NH 2 (XAO, X and O denote diaminobutyric acid and ornithine, respectively), and interpreted their results as indicating that the individual residues predominantly adopt a PPII conformation at room temperature. The results of Shi et al have been corroborated by numerous experimental and theoretical studies on short peptides, which all revealed a substantial PPII propensity for alanine (2,(4)(5)(6)(7)(8). This notion is also in perfect agreement with distributions that Serrano (25) and Avbelj and Baldwin (26) inferred from coil libraries, but at variance with a less restricted library investigated by Dobson and associates (27).…”
supporting
confidence: 53%
“…T he unfolded state of peptides and proteins has been the subject of an increasing number of experimental and theoretical studies (1)(2)(3)(4)(5)(6)(7)(8)(9), owing to the discovery of naturally disordered, although biologically functioning, proteins and peptides (9), and the general relevance for a thorough understanding of the protein folding process. In this context, the possible existence of local residue structure would certainly affect the initial phase of the folding process (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Raman microscopy is a valuable tool in assisting biocrystallographers [12,13], and it is now available on synchrotron beamlines [14]. Many Raman studies have been conducted to detect polyproline II conformation in oligo- [15,16], poly-peptides and proteins [17]. Raman optical activity [18] and UV-Raman resonance spectroscopy [19] are also valuable tools to extract secondary structural details.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A study published in 2004, for example, showed that AXA tripeptides (X being valine, tryptophan, histidine, and serine) predominantly adopt an extended β strand conformation, while AXA tripeptides, for which X is lysine and proline, prefer a polyproline II like (PPII) structure. 21 In contrast, the Ala Phe Ala sequence was found to fold as an inverse γ turn in water. 22 Therefore, it is not unambiguously clear whether the extended conformation observed for 1 and 2 is a direct consequence of peptide glycosylation.…”
Section: Conformational Analysis Of the Free α-N-linked Glycopeptidesmentioning
confidence: 99%